Jungfrauen in Waffen: Camilla Virgo, Iuturna Virago - Köves-Zulauf, Thomas (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
The paper starts with the analysis of the ambiguous figure of the “Italic Amazon” Camilla in the Aeneis. Two main factors are analysed, the role of the spear in the life of this “armed virgin” and her relations with natural surroundings, especially with rivers like the Amasenus and with lakes and marshes generally. Both prove to be fateful. The second factor is also noticeable with the other armed virgin of the Aeneis, Iuturna, who emerges as an upgraded and contrasting parallel to Camilla. Iuturna virago shows similarities with another famous virago of Latin literature, the Paluda virago of Ennius, and this gives an opportunity to evoke other women of the Roman tradition in connection with rivers and marshes, a phenomenon which proves to be a suitable topic for future exanimation.